2016
DOI: 10.1111/1750-3841.13428
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on Peptide‐Bound Pyrraline Formation and Elimination in the Maillard Reaction Using Single‐ and Multiple‐Response Models

Abstract: Pyrraline, an advanced glycation end product (AGE), is related to some chronic diseases and can be employed as an indicator for heat damage in food processing. In this study, the impact of changing the reactant concentration and ratio on the kinetic parameters describing peptide-bound pyrraline (pep-pyr) formation and elimination was evaluated in the Lys-Gly/glucose model systems, with microwave heating treatment ranging from 120 to 200 °C. The maximum pep-pyr concentration increased as follows: 200 °C ˂ 180 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…However, at >0.50% Na + , the pyrraline concentration decreased gradually. In this study, the maximum pyrraline concentration was obtained at 140 °C, consistent with our past findings [27,28].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…However, at >0.50% Na + , the pyrraline concentration decreased gradually. In this study, the maximum pyrraline concentration was obtained at 140 °C, consistent with our past findings [27,28].…”
Section: Resultssupporting
confidence: 93%
“…In conventional cooking, the temperatures of the thermal-induced MR range between 100 and 300 °C [25]. Certain AGEs, such as CML and pyrraline, are likely to form at 120–200 °C [26,27,28]. Some studies [29,30,31,32,33] have reported that the sodium content (expressed as a percentage of mass concentration) ranges between 0.00% and 1.00% in foods, including packaged, commercially processed, and restaurant foods.…”
Section: Methodsmentioning
confidence: 99%
“…The history of the peptide-based Maillard research comes back to the early 1990s, when Smith and Thornalley proposed the simplest dipeptide hippuryl-lysine model to monitor the degradation of Amadori products accompanied with formation of CML [ 263 , 264 ]. Later, longer peptides (representing artificial [ 265 , 266 , 267 , 268 ] and natural [ 266 , 269 , 270 , 271 ] protein sequences) were employed to address kinetic and mechanistic aspects of glycation adduct formation, structure of novel products [ 265 , 266 , 267 , 268 , 272 ], and influence of reaction conditions on AGE patterns [ 269 , 273 , 274 , 275 ]. To understand the mechanisms of AGE formation in such in vitro glycation model systems, and to dissect individual pathways of advanced glycation, analysis of peptide products can be complemented by quantification of carbohydrate [ 47 ] and α-dicarbonyl [ 276 ] intermediates.…”
Section: Part 2 New Prospectives In Maillard Proteomicsmentioning
confidence: 99%
“… Synthesis of Amadori-modified peptides by global glycation approach and building block strategy. After selective deprotection of the site to be glycated, Amadori moiety can be introduced directly by incubation with reducing sugar [ 273 ] or via the Lobry de Bruyn reaction with acetonide-protected hexodiulose (2,3:4,5-di- O -isopropylidene-aldehydo-β- d -arabino-hexos-2-ulo-2,6-pyranose) in presence of cyanoborohydride in methanol-isopropanol-water mixture (2:2:1 by volume) [ 274 ]. Alternatively, glycated moiety can be introduced with an acetonide-protected N ε -Boc- N ε -fructosyl- N α -Fmoc-lysine building block [ 272 ].…”
Section: Figurementioning
confidence: 99%
“…1 AGEs are a diverse group of substances formed by reactions between biological molecules with different compositions and structures, such as reducing sugars, dicarbonyl compounds, amino acids, peptides, proteins, lipids and nucleic acids. [2][3][4][5][6] Studies suggest that the intake of dietary AGEs can promote the accumulation of advanced glycation end products in the human body. [7][8][9] Moreover, other studies indicate that ingestion of high levels of dietary AGEs can have an adverse impact on human health, which is linked to their ability to promote inammation, oxidative stress, diabetes, and kidney damage.…”
Section: Introductionmentioning
confidence: 99%